An overview of radiolabeled amino acid tracers in oncologic imaging - Jain, Sanchay; Dhingra, Vandana Kumar (Frontiers in Oncology, 2023)
Molecular imaging has witnessed great progress in the field of oncology over the past few decades. Several radioactive tracers, especially 18F-FDG (Fluorine18 - labelled fluorodeoxyglucose) have found widespread clinical applications in oncologic imaging. However, 18F-FDG has certain limitations which result in important pitfalls and cause diagnostic dilemma. In recent times ,radiolabelled amino acid (AA) tracers are particularly promising in these areas where utility of 18F-FDG PET/CT (Positron emission tomography with computed tomography) imaging has been limited. These include evaluation of brain tumors, neuroendocrine tumors, and prostate cancer. Radiolabelled AA tracers such as 18F-FDOPA, 18F-FET have found wide applications in brain tumor imaging which, unlike 18F-FDG concentrate in the tumor tissue to a greater extent than normal brain tissue , thus providing accurate information about tumor volume and boundaries. 18F-FDOPA is also useful in evaluation of neuroendocrine tumors (NETs). Tracers such as 18F-FACBC (Fluciclovine) and 18F-FACPC are used in imaging of prostate cancer and provide valuable information of locoregional, recurrent and metastatic disease. Key Words : Radiolabelled , Amino Acid , PET/CT, Imaging, Oncology.